Insights into differences in residents' attitudes : tourism impacts and support for future development - Soldić Frleta, Daniela (Array, 2020)
This study investigates the differences in residents’ perceptions of various tourism impacts as well as residents’ level of support for future tourism development with regard to their employment status (employed in tourism, employed in other industries, and others: students, unemployed persons, retirees). Moreover, the objective was to find out in what way those perceptions influence the residents’ level of support for future tourism development. The results show that there are statistically significant differences in perceptions of economic, socio-cultural, environmental and overall tourism impacts between the three groups of stakeholders. Respondents working in tourism expressed the strongest support for future development, while students, unemployed persons and retired residents tended to be less supportive. The main contribution of this study lies in the insights it provides into the attitudes of different groups of destination stakeholders regarding tourism impacts as well as into their support for future tourism development.